2015
DOI: 10.1002/jctb.4838
|View full text |Cite
|
Sign up to set email alerts
|

Lactic acid production on a combined distillery stillage and sugar beet molasses substrate

Abstract: BACKGROUND: Utilization of wastes and industrial by-products for production of valuable bio-based chemicals has economic and environmental advantages. The aim of this study was to investigate utilization of two industrial by-products, distillery stillage and sugar beet molasses combined as a substrate for lactic acid and biomass production. A selection of the most appropriate lactic acid bacteria that could effectively utilize this waste substrate was performed. In addition, the effect of initial sugar concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The ML could provide valuable nutrients for lactic acid fermentation. 35 In contrast, SSL had worse fermentation quality than the control, as evidenced by higher acetic acid (P = 0.001) and ammonia-N (P < 0.001) content, and the lower ratio of lactic acid to acetic acid (P = 0.038). On the other hand, all silages exceeded the pH threshold of 4.2 for well preserved silage, 36 which indicated poor fermentation quality.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The ML could provide valuable nutrients for lactic acid fermentation. 35 In contrast, SSL had worse fermentation quality than the control, as evidenced by higher acetic acid (P = 0.001) and ammonia-N (P < 0.001) content, and the lower ratio of lactic acid to acetic acid (P = 0.038). On the other hand, all silages exceeded the pH threshold of 4.2 for well preserved silage, 36 which indicated poor fermentation quality.…”
Section: Resultsmentioning
confidence: 87%
“…As expected, compared with the control, ML improved the fermentation quality, as evidenced by lower pH ( P < 0.001), and higher lactic acid content ( P < 0.001) as well as the ratio of lactic to acetic acid ( P < 0.001). The ML could provide valuable nutrients for lactic acid fermentation 35 . In contrast, SSL had worse fermentation quality than the control, as evidenced by higher acetic acid ( P = 0.001) and ammonia‐N ( P < 0.001) content, and the lower ratio of lactic acid to acetic acid ( P = 0.038).…”
Section: Resultsmentioning
confidence: 96%
“…Panesar et al [37] reported the production of 33.73 g•L −1 L-LA using L. casei, while Taleghani et al [38] reported a value of 32.1 g•L −1 when whey was fermented by L. bulgaricus. Molasses derived either from sugarcane or sugar beets fermentation to lactic acid has also been investigated, using various LAB strains [39][40][41]. In the recent work of Sun et al [41], a microbial consortium in which Clostridium sensu stricto was the predominant strain was tested for sugarcane molasses fermentation to lactic acid.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, lactic acid bacteria are amongst the most commonly used microorganisms for the production of fermented functional food products due to their health promoting activity and their capacity for stabilising and improving the safety of food products (Speranza, Bevilacqua, Sinigaglia, & Corbo, 2012;Paiva et al, 2016;Viana de Souza & Silva Dias, 2017). However, they are fastidious microorganisms in terms of nutrient requirements (Subhasree & Bhakyaraj, 2013;Vázquez et al, 2016;Mladenoviae, Djukiae-Vukoviae, Kociae-Tanackov, Pejin, & Mojoviae, 2016). This work is aimed at evaluating the potential of rice fractions obtained by controlled debranning for supporting the growth of two human-isolated probiotic Lactobacillus sp.…”
Section: Accepted Manuscriptmentioning
confidence: 99%